2012
DOI: 10.1016/j.str.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics Associated with Intermediate Formation in an Archetypal Conformational Disease

Abstract: SummaryIn conformational diseases, native protein conformers convert to pathological intermediates that polymerize. Structural characterization of these key intermediates is challenging. They are unstable and minimally populated in dynamic equilibria that may be perturbed by many analytical techniques. We have characterized a forme fruste deficiency variant of α1-antitrypsin (Lys154Asn) that forms polymers recapitulating the conformer-specific neo-epitope observed in polymers that form in vivo. Lys154Asn α1-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Our NMR studies followed the polymerisation of Queen's (Lys154Asn) α 1 -antitrypsin under physiological conditions or in urea. Intermediate (M*) formation under physiological conditions was associated with highly native-like behaviour with changes in a few key motifs [14]. Global changes were observed in urea consistent with more widespread unfolding, in keeping with data from hydrogen-deuterium exchange [27].…”
Section: Controversies On the Structure Of The Pathological Polymersupporting
confidence: 75%
See 2 more Smart Citations
“…Our NMR studies followed the polymerisation of Queen's (Lys154Asn) α 1 -antitrypsin under physiological conditions or in urea. Intermediate (M*) formation under physiological conditions was associated with highly native-like behaviour with changes in a few key motifs [14]. Global changes were observed in urea consistent with more widespread unfolding, in keeping with data from hydrogen-deuterium exchange [27].…”
Section: Controversies On the Structure Of The Pathological Polymersupporting
confidence: 75%
“…Our work suggests that the Z mutation perturbs its local environment (breach region, Fig. 1A) to favour population of an unstable intermediate that we termed M* [8] in which β-sheet A opens [2,8] and the upper part of helix F unwinds [9,13,14]. The patent β-sheet A can then accept insertion of the reactive site loop motif.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…During the activation to intermediate, there is a change in far-UV circular dichroic signal, intrinsic tryptophan fluorescence, the interaction with ANS (8-anilinonaphthalene-1-sulfonic acid) or bis-ANS (4,4 -dianilino-1,1 -binaphthyl-5,5 -disulfonic acid) dyes [14,17], ion mobility mass spectrum collision crosssectional area [18] and NMR cross-peaks [19]. While denaturant can induce polymerization at concentrations that favour population of an unfolding intermediate state (I denat ) [6,20], observations indicate that there are multiple pathways favoured depending on the manner in which polymers are formed, and as a result intermediate ensembles represented by I pol and I denat could be structurally distinct [19].…”
Section: Introductionmentioning
confidence: 99%
“…While denaturant can induce polymerization at concentrations that favour population of an unfolding intermediate state (I denat ) [6,20], observations indicate that there are multiple pathways favoured depending on the manner in which polymers are formed, and as a result intermediate ensembles represented by I pol and I denat could be structurally distinct [19]. In support of this, it has recently been shown that polymers produced in the presence of denaturant lack an epitope that is expressed on polymer obtained from patient samples [18,21].…”
Section: Introductionmentioning
confidence: 99%